Uncontrolled Generation in Nine-Phase Machine Drive - Stare, Živa; Fišer, Rastko; Drobnič, Klemen (XXVIII. Symposium Electromagnetic Phenomena in Nonlinear Circuits (EPNC 2024): Conference Proceedings, 2025)
Uncontrolled generation (UCG) is a phenomenon that occurs in electric drives when operating in a field‑weakening and a gate signal is suddenly removed from switches. When the induced voltage is higher than the DC link voltage, a path is created for current to flow from the machine through the freewheeling diodes of the converter back into the DC link. While UCG is commonly associated with three-phase drives, the topology of some multiphase machine drives—comprising separate three-phase winding sets—enables the manifestation of UCG in only one winding set. This arrangement allows the remaining two winding sets to facilitate post-fault operation.